Ubiquitous Learning Environment and Technologies: A Review - Mohd Tahir, Zurainee; Haron, Haryani; Kaur, Jasber (International Journal of Engineering and Technology, 2018)
In recent years, the education landscape is rapidly changing due to the advancement of information and communication technology infrastructure. The paradigm shift in educational landscape has changed the learnerâ€™s behaviors from passive to active in their learning process. Ubiquitous learning is a new learning environment that integrates the benefit of e-learning and mobile learning. The technology plays an important role in supporting ubiquitous learning and a proper technology configuration to obtain learning information is a must. The support for those technology needs in ubiquitous learning is coming from computer-based technologies. The aim of the paper is to performed literature review for ubiquitous learning environment and providing specific information about ubiquitous learning concepts and the criteria that needed in the future research. It begins by briefly describing the transformation of learning environment, the concepts of ubiquitous learning, the characteristics of ubiquitous learning, the technical structure of ubiquitous learning and ubiquitous technologies devices in ubiquitous learning environment is also described. Finally, the comparative studies of ubiquitous learning environment framework are compared and discussed to further enhance the understanding of ubiquitous learning environment. The result showed that technology usage is vital within learners and educators in learning process. Therefore, it is important to have a medium that can be used to improve learning process to be more effective and the most important part to take a look for before implementing new technology into academic learning is the readiness of the infrastructure.Â Â